2021
DOI: 10.3390/polym13193368
|View full text |Cite
|
Sign up to set email alerts
|

Material Anisotropy in Additively Manufactured Polymers and Polymer Composites: A Review

Abstract: Additive manufacturing (AM) is a sustainable and innovative manufacturing technology to fabricate products with specific properties and complex shapes for additive manufacturable materials including polymers, steels, titanium, copper, ceramics, composites, etc. This technology can well facilitate consumer needs on products with complex geometry and shape, high strength and lightweight. It is sustainable with having a layer-by-layer manufacturing process contrary to the traditional material removal technology—s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 101 publications
(159 reference statements)
0
42
0
2
Order By: Relevance
“…In fact, the shrinkage along the axial dimension is more pronounced than the one measured along the radial dimension. This is due to the nature of the DLP printing working principle itself [41,42]: while on the layer plane, the material behaviour can be assumed to be isotropic if the used slurry had been thoroughly homogenised; along the building direction, more factors such as an optimal layer recovery influence the homogenisation of the material and, consequently, the material behaviour along it. Moreover, the final relative density obtained for the sintered samples, together with SEM images taken for trial 1 and trial 6, are shown in Figure 10 and categorised in terms of dwell time.…”
Section: Sintered Samples Characterisation and Numerical Model Valida...mentioning
confidence: 99%
“…In fact, the shrinkage along the axial dimension is more pronounced than the one measured along the radial dimension. This is due to the nature of the DLP printing working principle itself [41,42]: while on the layer plane, the material behaviour can be assumed to be isotropic if the used slurry had been thoroughly homogenised; along the building direction, more factors such as an optimal layer recovery influence the homogenisation of the material and, consequently, the material behaviour along it. Moreover, the final relative density obtained for the sintered samples, together with SEM images taken for trial 1 and trial 6, are shown in Figure 10 and categorised in terms of dwell time.…”
Section: Sintered Samples Characterisation and Numerical Model Valida...mentioning
confidence: 99%
“…Consequently, it is widely used in aerospace, medical devices, thermal barrier coatings, piezoelectric components, catalysts, and ceramic capacitors, etc 10–12 . In particular, with the advent of the age of 5G communication, ZrO 2 with high toughness, high wear resistance, and low electromagnetic shielding has become the preferred material for electronic communication devices such as mobile phones 13,14 . High‐performance ZrO 2 ceramics require high‐quality ZrO 2 powder, so the preparation of ultra‐fine, well‐dispersed, and crystal‐stable nano‐ZrO 2 powder is a hot spot in current ceramic research 15 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In particular, with the advent of the age of 5G communication, ZrO 2 with high toughness, high wear resistance, and low electromagnetic shielding has become the preferred material for electronic communication devices such as mobile phones. 13,14 High-performance ZrO 2 ceramics require high-quality ZrO 2 powder, so the preparation of ultra-fine, welldispersed, and crystal-stable nano-ZrO 2 powder is a hot spot in current ceramic research. 15 Tourmaline is a silicate with a glass luster, transparent or translucent.…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее ярко проблему анизотропии можно проследить по результатам стандартных испытаний на растяжение и изгиб, в которых одна группа образцов располагается на столе плашмя (и разрушающая нагрузка работает на деформацию всех слоев одновременно), а другая группа -вертикально (и разрушающая нагрузка вызывает быстрый разлом образца по слоям). Так, в обзорной работе [3] указывается разность прочности в этих двух направлениях от 30 до 77 % для разных пластиков (в первую очередь полиамидов и ABS-пластика) при испытаниях на растяжение.…”
Section: Introductionunclassified
“…В то же время анизотропия характерна и для «наполненных» филаментов -ABS с короткими волокнами до 82 % при растяжении [3] и от 45 до 207 % при изгибе [4]. В исследовании [5] показана анизотропия образцов из чистого полиамида (PA) и полиамида с короткими волокнами (PA/CF), которая составила 175 и 244 % соответственно при испытаниях на растяжение, а при испытаниях на изгиб разность прочности в двух направлениях составила 205 % для PA и 317 % для образцов из PA/CF.…”
Section: Introductionunclassified